G236(P) Introduction of a transcutaneous bilirubinometer into children's ED – a good initiative?. (27th April 2016) - Spence, J; Bevan, C; Walton, E
Abstract : Aims: Neonatal attendances to Children's Emergency Departments (CED) are an increasing issue, with jaundice a common presenting problem. Assessment of the level of jaundice has traditionally been by a blood test. This not only has the disadvantages of distress, inconvenience and cost, but also exposes neonates to a busy CED for prolonged time periods. Would the introduction of a simple transcutaneous bilirubinometer into the department safely and accurately improve the delivery of our care? Methods: All neonates who presented to our CED between 17/09/15 and 18/11/15 requiring investigation for jaundice had both a transcutaneous bilirubinometer (three readings taken on the sternum) and a laboratory analysis of serum bilirubin. We compared results obtained from both measurements, determined what proportion of babies could avoid a blood test (in accordance with NICE guidance on the use of transcutaneous bilirubinometers) and whether blood results changed management. The study is ongoing. Results: Figure 1 19 babies presented with jaundice (two were excluded as no serum bilirubin results were available). Babies ranged from gestational ages of 36 to 41 weeks, presenting age range 1 to 28 days. 7 of these were for jaundice alone, referred from community midwives. 12 presented with both jaundice and another complaint e.g. weight loss, poor feeding. On average, the bilirubinometer result was within 12% of the serum bilirubin (mean = 12%, range 1%–30%). 12/17 (71%) had transcutaneous bilirubin readings below 250 nmol/L. In one case only, serum results changed management – initiating phototherapy. However, given transcutaneous levels were above 250nmol/L, in line with NICE guidelines, blood tests would have been initiated regardless. 3/12 (25%) were admitted immediately following high readings, improving patient flow and efficiency. Conclusion: In our initial population, up to 71% of babies could have avoided the need for blood tests, offered simple advice and feeding support. Furthermore, if a community transcutaneous bilirubinometer had been available, potentially 24% of these attendances at CED could have been avoided altogether. When used in line with NICE guidance, the transcutaneous bilirubinometer is an easy to use, safe, non-invasive and accurate method of measuring jaundice in a neonate.